Exploring the Concept of Nafs in Islamic Counseling: A Comprehensive Analysis of Philosophical Foundations and Implications for Education - Apriyanti; Fadila; Syamsul Rizal; Rosyada, Moh. Faza (HEUTAGOGIA: Journal of Islamic Education, 2023)
This study comprehensively analyzes the concept of Nafs (self or soul) within Islamic counseling, bridging Islamic teachings with psychological principles. Utilizing a literature review methodology, it systematically collates and examines scholarly sources to explore the philosophical underpinnings and practical applications of Nafs in Islamic educational psychology. The research identifies three interpretations of Nafs: the entirety of an individual, the soul, and a container for ideas and desires. These interpretations are contextualized within the frameworks of guidance and counseling, examining their roles in shaping human behavior, intrinsic motivation, and subconscious influences. The study reveals the importance of Nafs in fostering holistic development in Islamic education, emphasizing moral, spiritual, and psychological dimensions. While acknowledging the existing literature's diverse scholarly perspectives and limitations, this research underlines the need for further empirical studies on Nafs’ practical applications in various educational settings. It concludes that an integrated approach to Islamic counseling, encompassing academic, moral, and spiritual aspects, is vital for nurturing a morally and spiritually intelligent generation, aligning with Islamic values.